The velveteen rabbit ; or, How toys become real - Bianco, Margery Williams, 1881-1944.; Nicholson, William, 1872-1949 (New York : Avon, 1975)
By the time the velveteen rabbit is dirty, worn out, and about to be burned, he has almost given up hope of ever finding the magic called Real.
Kirkus Reviews
New York Times Book Review
6.1
3-6
AD1050L
Accelerated Reader AR
Keywords: Toys; Toys; Fiction; Fiction